Exploring the interplay between social connectedness, job control, and organizational commitment: the mediating role of work engagement among Chinese teachers - Xing Li; Yong Xu; Dan Huang (BMC Psychology)
Abstract This study investigated the factors influencing teachers’ organizational commitment in China. We employed a survey design with a sample of 506 full-time teachers from various public middle and high schools across mainland China. Social connectedness, job control, and work engagement were measured using self-reported scales. Structural equation modeling (SEM) was utilized to examine the hypothesized relationships. The results indicated that social connectedness and job control were directly associated with higher levels of organizational commitment among teachers. Furthermore, work engagement played a mediating role in these relationships. Specifically, teachers who felt more connected to their colleagues and had greater control over their work reported higher levels of work engagement, which, in turn, predicted stronger organizational commitment. These findings highlight the importance of fostering a supportive and collaborative school environment to cultivate social connectedness and provide teachers with greater autonomy and decision-making opportunities to enhance job control. By nurturing these factors, schools can promote work engagement, ultimately leading to a more dedicated and committed teaching workforce.